Evolution of H-shaped dielectric resonator antenna for 5G applications - S. Z. N. Zool Ambia; M. H. Jamaluddin; M.R. Kamarudin; J. Nasir; R.R. Selvaraju (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, an H-shaped Dielectric Resonator Antenna (DRA) with a Microstrip Slot Aperture (MSA) is presented and investigated at 26 GHz. In order to widen the bandwidth operation, the slot aperture feeding technique is applied. The designed DRA with relative permittivity, εr of 10 is mounted on a Duroid substrate with a relative permittivity, εr of 2.2, loss tangent of 0.0009 and a thickness of 0.254mm. The proposed antenna with overall size of 20 x 20 x 5.27 mm3 achieves good impedance matching, gain of 7.61 dB and good radiation patterns. An impedance bandwidth of 21.44%, covering the frequency range from 24.72 GHz to 30.62 GHz made the antenna has potential for millimeter wave and 5G applications.